2012
DOI: 10.1002/fuce.201200088
|View full text |Cite
|
Sign up to set email alerts
|

Proton and Protonic Species: The Hidden Face of Solid State Chemistry. How to Measure H‐Content in Materials?

Abstract: The first objectives of Chemistry are the description of the reactions and the determination of the composition of each compound involved in a process. Solid State Chemistry tries to establish the composition and the structure, the (micro/nano)structure as well as the relationship between composition, structure, and material properties. In the case of Hydrogen element, most of the literature data do not follow this approach: the contents of protons and associated protonic species are rarely measured. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 140 publications
6
42
0
Order By: Relevance
“…Coupled to the H 2 O signal between 4,500 and 5,200 cm −1 , no H 2 was detected at 4,100 cm −1 , which is consistent with the absence of H 2 signal in Raman spectra. However, a small presence of H 2 will not change the H 2 O quantification because the calibrations are not established at these wavenumbers for both Raman and FTIR spectroscopies.…”
Section: Resultssupporting
confidence: 78%
“…Coupled to the H 2 O signal between 4,500 and 5,200 cm −1 , no H 2 was detected at 4,100 cm −1 , which is consistent with the absence of H 2 signal in Raman spectra. However, a small presence of H 2 will not change the H 2 O quantification because the calibrations are not established at these wavenumbers for both Raman and FTIR spectroscopies.…”
Section: Resultssupporting
confidence: 78%
“…The formation of the BaLiF 3 low melting phase (T m = 857°C) is also possible in the BaCe x Zr 0.8 -x Y 0.2 O 3 -δ /LiF system: (8) It should be noted that, according to the data of Tu et al [103], The addition of LiF leads to structural instability of BaCe 0.8 ⎯ x Zr x Y 0.2 O 3 -δ under a СО 2 atmosphere (400-900°С) even at high zirconium con 0. 2 [84] a The presence of impurity phases was detected by XRD, scanning electron microscopy, and ceramic samples electron microscopy. b BaCe 0.8 Y 0.2 O 3 -δ sintered at 1400°C without modifier has tetragonal perovskite structure with small impurity of rhombohedral phase; for BaCe 0.8 Y 0.2 O 3 -δ + 0.5 wt % NiO, rhombohedral modification becomes prevalent, while monoclinic one is an impurity phase.…”
Section: Bacementioning
confidence: 99%
“…High temperature proton conducting electrolytes are a wide series of oxide materials showing proton conduction in the presence of hydrogen containing components of a gas atmosphere [1,2]. Since the dis covery of proton conduction in materials with perovskite structure (Iwahara et al, 1980s [3,4]), it is also revealed at present in oxide systems with structure of brownmillerite [5,6], scheelite [7,8], pyrochlore [9], and even fluorite [10].…”
Section: Introductionmentioning
confidence: 99%
“…H and the metals whose electronegativities are well smaller than H, such as alkali and alkaline earth metals, form the hydrides that have the ionic bonding nature, and the hydrogen‐related vibrational modes appear between 300 and 1100 cm −1 . Raman scattering measurements have found that H 2 O and H 2 molecules are captured in amorphous silica (SiO 2 ) by observing the O–H stretching modes at near 3400 cm −1 and the intramolecular stretching mode of H 2 (H 2 vibron) at near 4200 cm −1 , respectively . Interestingly, it has been revealed that rare gases form compounds with H 2 under high pressures, and the H 2 vibrons possess higher wavenumbers than pure H 2 .…”
Section: Introductionmentioning
confidence: 99%